PROSEDUR MEMPEROLEH IZIN PERUBAHAN PENGGUNAAN TANAH PERTANIAN MENJADI NON-PERTANIAN - , CANGGIH MUHAMMAD R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The author wants to identify requirement and process of land usage conversion permit, so it can be applied in daily life of society and to identify obstacle face. Subjective goal of this field work practice is one of obligatory courses that should be followed as requirement to obtain degree Ahli Madya Hukum from Diploma 3 Law Program, Vocational School, Gadjah Mada University. Meanwhile its objective goal is to understand comprehensively correlation between theory and practice of law science that eventually to aid author in real work field. Benefit of field work practice is to apply knowledge obtained from courses, to add insight and theoretical and practical knowledge that has not been obtained in courses. Conclusion drawn is that land usage conversion permit is land use permit that individual should have to convert agricultural land usage to non agricultural usage for house construction with maximal area of 5000m2. The permit is given gradually of each maximally 600m2. Agricultural land is rice-field land or lands sue for agriculture or non urbanized land. Non agricultural land is land not intended for agriculture or built land (Settlement, market or shop, park, square, cemetery, and so on).